Teacher Professionalism and Its Relationship with Student Learning Achievement in Fiqh Subject at MAS Nurul Haq Rite - Hafid, Abdul; Nurmalah (MANDAILING GLOBAL EDUKASIA, 2025)
This study investigates the relationship between Fiqh teacher professionalism and student learning achievement at MAS Nurul Haq Rite, Ambalawi District, Bima Regency. Teacher professionalism is defined as the expertise, authority, and quality of a Fiqh teacher's work, encompassing their competence in planning, subject matter mastery, teaching implementation, and assessment skills. Student learning achievement is measured by academic outcomes reflected in grades. Employing a mixed-methods approach combining library research and field research, data was collected through questionnaires administered to randomly selected 10th and 11th-grade students, as well as through observation, interviews, and documentation studies. The collected data was analyzed using the product moment formula and the coefficient of determination to assess the correlation and contribution of teacher professionalism to student learning outcomes. The research findings demonstrate a positive and significant relationship between Fiqh teacher professionalism and student learning achievement at the studied institution. Statistical analysis reveals that teacher professionalism accounts for 50% of the variance in student learning achievement in Fiqh. This indicates that the level of a Fiqh teacher's professionalism is a substantial determinant of student academic success in this subject, while the remaining 50% of the variance is influenced by other factors not explored in this study. These results underscore the critical role of teacher professionalism in fostering improved learning outcomes in Islamic jurisprudence.